Crystallographic evidence and spin activation for the Russian-doll-type metallofullerene Sc4C2@C80. Issue 74 (17th August 2020) - Nie, Mingzhe; Meng, Haibing; Zhao, Chong; Lu, Yuxi; Zhang, Jie; Feng, Lai; Wang, Chunru; Wang, Taishan
Abstract : We report the unambiguous crystallographic evidence, cluster configuration and oxidation properties for the Russian-doll-type metallofullerene Sc4 C2 @Ih -C80 . Abstract : We report unambiguous crystallographic evidence for the Russian-doll-type metallofullerene Sc4 C2 @Ih -C80 . 45 Sc NMR further demonstrates the tetrahedron arrangement of the Sc4 C2 cluster. Moreover, the electrochemical test reveals the stable oxidation state of Sc4 C2 @C80 . Hence, the Sc4 C2 @C80 cation radical was studied by electron spin resonance spectroscopy. These results provide better understanding for the previously less-explored Sc4 C2 @C80 .